2022
DOI: 10.1093/asj/sjac270
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Percutaneous Superficial Temporal Arterial Hyaluronidase Injection for Hyaluronic Acid Filler–Induced Necrosis of Frontotemporal Skin and/or the Ipsilateral Scalp With Subsequent Alopecia

Abstract: Background Necrosis of frontotemporal skin and/or the ipsilateral scalp with subsequent alopecia after hyaluronic acid (HA) filler injection into the temple are rare and newly reported complications, with superficial temporal artery (STA) embolization suspected as the major pathological mechanism. The main treatment currently is intralesional hyaluronidase (HAase) injection, but the effectiveness of percutaneous superficial temporal arterial HAase injection still lacks consensus. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…After 2-3 months, the hair that falls off gradually grows back, with hair density returning to normal levels by 5-6 months. 18 Subcutaneous injection of hyaluronidase is a common treatment method for blindness caused by facial filling. In addition, retrobulbar injection of hyaluronidase is the standard treatment for hyaluronidase to block the ophthalmic artery, which has proved to be somewhat effective in practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After 2-3 months, the hair that falls off gradually grows back, with hair density returning to normal levels by 5-6 months. 18 Subcutaneous injection of hyaluronidase is a common treatment method for blindness caused by facial filling. In addition, retrobulbar injection of hyaluronidase is the standard treatment for hyaluronidase to block the ophthalmic artery, which has proved to be somewhat effective in practice.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] However, emboli-induced skin necrosis and ptosis usually show a better prognosis after appropriate treatment. 17,18 Only a few cases of severe necrosis can be treated using full-thickness skin grafts. 15 In addition to ordinary fillers, we found that lidocaine and adrenaline solutions can induce intravascular embolisms and ultimately elicit blindness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation